2018
DOI: 10.22159/ajpcr.2018.v11i2.17096
|View full text |Cite
|
Sign up to set email alerts
|

Content of Nutrients Component and Fatty Acids in Chia Seeds (Salvia Hispanica L.) Cultivated in Ecuador

Abstract: Objective: The aim of this work was to determine the fatty acids content in chia seeds oil (Salvia hispánica L.) sample cultivated in Ecuador.Methods: Chia oil was obtained from chia seeds using the cold pressing method. Methyl esters fatty acids (FAME) analysis was carried out using the gas chromatography (GC) method with a mass selective detector (MSD) and using the database Library NIST14.L to identify the compounds present in the oil of chia seed. Results:Methyl esters fatty acids were identified from chia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In addition, composite flour (75:25) was significantly different from all other composite blends. FV reflected cooked starch stability and is commonly used as a quality criterion for pasting properties (Alamu et al, 2017), and its lowering tendency could also be attributed to interactions between the starch, fat, and protein contents of the blends (Carrillo et al, 2018; Kiin-Kabari et al, 2015). FV as it shows material's ability to form a viscous paste (Iwe et al, 2017), a small amount of inclusion of chia seeds into composite flour blend (95:05) significantly affected FV as compared to CF.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, composite flour (75:25) was significantly different from all other composite blends. FV reflected cooked starch stability and is commonly used as a quality criterion for pasting properties (Alamu et al, 2017), and its lowering tendency could also be attributed to interactions between the starch, fat, and protein contents of the blends (Carrillo et al, 2018; Kiin-Kabari et al, 2015). FV as it shows material's ability to form a viscous paste (Iwe et al, 2017), a small amount of inclusion of chia seeds into composite flour blend (95:05) significantly affected FV as compared to CF.…”
Section: Resultsmentioning
confidence: 99%
“…All samples were statistically different (P<0.05) from each other. A similar study by Cardenas et al [24] showed that the high carbohydrate composition in chia seed cultivated in Ecuador was 31.46%. Besides, Jacqueline et al [25] found that monosaccharides such as β-D-xylose, α-D-glucose, and α-D-glucoronic acids were obtained in chia seed through acid hydrolysis.…”
Section: Chemical Compositionmentioning
confidence: 57%
“…Chia seed has high oil content primarily consisting of αlinolenic acid, a healthy form of fat that could improve the sausage's fatty acid profiles [1] [24]. The high-fat content in the sample with chia seed powder substitutions might also be caused by the oil holding capacity (OHC) of the chia seed (11.67 g/g) and its gum (25.79g/g).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Another "novel" and "healthy" functional food ingredient, found in chia seeds that have gained increasing interest due to their unique nutritional properties [21], contains considerable amounts of carbohydrates (42,12 %), especially unsaturated fat (30.74%), dietary fiber (34.4%) and protein (16.54%) [22]. Furthermore, it contains antioxidants, minerals and vitamins [23].…”
Section: Introductionmentioning
confidence: 99%